Age-related anabolic resistance after endurance-type exercise in healthy humans - Durham, William J. (Federation of American Societies for Experimental Biology, 2010)
Age-related skeletal muscle loss is thought to stem from suboptimal nutrition and resistance to anabolic stimuli. Impaired microcirculatory (nutritive) blood flow may contribute to anabolic resistance by reducing delivery of amino acids to skeletal muscle. In this study, we employed contrast-enhanced ultrasound, microdialysis sampling of skeletal muscle interstitium, and stable isotope methodology, to assess hemodynamic and metabolic responses of older individuals to endurance type (walking) exercise during controlled amino acid provision. We hypothesized that older individuals would exhibit reduced microcirculatory blood flow, interstitial amino acid concentrations, and amino acid transport when compared with younger controls. We report for the first time that aging induces anabolic resistance following endurance exercise, manifested as reduced (by ∼40%) efficiency of muscle protein synthesis. Despite lower (by ∼40–45%) microcirculatory flow in the older than in the younger participants, circulating and interstitial amino acid concentrations and phenylalanine transport into skeletal muscle were all equal or higher in older individuals than in the young, comprehensively refuting our hypothesis that amino acid availability limits postexercise anabolism in older individuals. Our data point to alternative mediators of age-related anabolic resistance and importantly suggest correction of these impairments may reduce requirements for, and increase the efficacy of, dietary protein in older individuals. Durham, W. J., Casperson, S. L., Dillon, E. L., Keske, M. A., Paddon-Jones, D., Sanford, A. P., Hickner, R. C., Grady, J. J., Sheffield-Moore, M. Age-related anabolic resistance after endurance-type exercise in healthy humans.